How did its Charity Go? The Practice of Zakat Management in e-Commerce Platforms - Zaimah, Nely Rahmawati; Zaman, Akhmad Roja Badrus (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2024)
This study delves into the application of zakat within the realm of e-commerce platforms, specifically focusing on the accuracy and accountability of zakat calculation. It underscores the significance of assessing the precision and transparency of zakat collection and distribution within the digital landscape, particularly through platforms like Tokopedia. By employing a qualitative approach with investigative inquiry, the research facilitates a comprehensive comprehension of zakat practices within e-commerce. Data were gathered through thematic exploration, observation, and scrutiny of pertinent documents to ensure conformity with Sharia law. The research underscores the challenges associated with precise zakat calculation and accountability in reporting. Users necessitate clear guidelines for accurate zakat computation, including distinct benchmarks for gold and silver with regularly updated price parameters. Moreover, e-commerce platforms must guarantee transparency in zakat fund reporting. The establishment of policies for monitoring and supervising e-commerce platforms and integrated philanthropic entities is imperative. Additionally, the researcher advocates for further investigations to delve into user preferences concerning zakat practices and recommends collaborative endeavours among philanthropic bodies, governmental entities, and users to enhance charitable practices amidst the dynamic digital landscape.